Least likely to win a duke - Murdoch, Emily E. K. (Murdoch, Emily E. K. Wallflower Academy., 2023)
"Miss Pike's finishing school might be designed to find the most unconventional of debutantes a husband, but Gwendoline Knox didn't expect to literally bump into a duke on her first day! Let alone one as distractingly charming as Percy Deveraux. Gwen knows nothing can come of their flirtations, not with their different stations-or her scandalous secret! Still, she can't help wishing for more, even if that means confronting her past..."--